Stretchable flexible lithium ion battery and preparation method thereof

By adding elastic polymer to the positive and negative electrode slurry of lithium-ion batteries and using flexible PDMS materials, the problem that lithium-ion batteries are difficult to meet the multi-direction stretching requirements in human wearable devices is solved, and the normal charging and discharge of the battery under 20% stretching is achieved.

CN119833637AActive Publication Date: 2025-04-15浙江大学宁波国际科创中心 +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510046765.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-15
Estimated Expiration
2045-01-13

Smart Images

  • Figure CN119833637A_ABST
    Figure CN119833637A_ABST
Patent Text Reader

Abstract

The invention discloses a stretchable flexible lithium ion battery and a preparation method, and belongs to the technical field of electrochemical energy storage.The stretchable flexible lithium ion battery is characterized in that an elastic polymer is added into positive and negative electrode slurry to replace traditional polyvinylidene fluoride, so that the stretchability of the battery is improved; the positive and negative electrode slurry and the battery assembly mode can ensure that the battery is normally charged and discharged under the condition of 20% stretching, and a flexible battery can be prepared and used for designing wearable electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical energy storage, and in particular relates to a stretchable flexible lithium-ion battery and a preparation method thereof. Background Art

[0002] In recent years, with the trend of intelligent and integrated wearable devices, flexible wearable electronic technology has become a hot research field. With the rapid development of wearable devices, higher demands are placed on energy supply equipment. Supercapacitors or batteries are often used to supply energy for them. In order to cope with the use environment of stretching and deformation in the wearable environment of the human body, requirements are put forward for the stretchability of the battery and the adaptability of the power supply structure. However, traditional lithium-ion battery products are rigid, and the materials such as the battery electrodes, current collectors, and substrates are rigid and do not have the ability to withstand strain, making it difficult to apply them to power wearable devices. In addition, some flexible batteries can only bend the battery slightly and cannot be stretched. At the same time, they also have disadvantages such as complex production process and low energy density.

[0003] Chinese patent application CN118281371A discloses a method for preparing a leather-integrated fully flexible zinc-ion battery, which uses leather as a substrate, composites conductive polymers and zinc powder on both sides of the leather, and selects different current extraction materials and flexible outer packaging to make a flexible zinc-ion battery. Chinese patent application CN118645704A discloses a flexible battery with freely designed shapes and a preparation method, which uses aluminum-plated aramid and copper-plated aramid as positive and negative current collectors, respectively, and coats the surface with positive and negative electrode materials, and then assembles the negative electrode with the positive electrode to obtain fibrous positive and negative electrodes, arranges the fibrous positive and negative electrodes according to the required battery shape, transfers the pole ears, injects gel electrolyte, and finally seals to form a battery.

[0004] Although the above-mentioned related technologies can realize the flexibility of the battery, they can usually only realize a certain degree of bending or folding, and it is difficult to meet the stretching requirements in multiple directions. In common flexible battery designs, electrodes and electrolyte materials are prone to rupture or delamination when subjected to stretching, resulting in a sharp decline in battery performance. In common stretchable battery designs, only the stretchability of a single electrolyte, the stretchability of the current collector material, etc., or the stretchability of the battery pack structure can be achieved, and the stretchable battery design of the entire battery cannot be completed. If the battery can be stretched and can be charged and discharged under stretching, it will be very convenient for the application of wearable electronic devices, and can be designed according to the stretching requirements of different parts of the wearable electronic devices to cope with more complex human body environments. Therefore, it is necessary to provide a lithium-ion battery that can not only realize the flexibility of the battery, but also meet the needs of complex deformations such as stretching. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a stretchable flexible lithium-ion battery and a preparation method. The present invention adds elastic polymers to the positive and negative electrode slurries to replace the traditional polyvinylidene fluoride, thereby improving the stretchability of the battery. The positive and negative electrode slurries and the battery assembly method can ensure that the battery can be normally charged and discharged when stretched by 20%.

[0006] To achieve the above object, the present invention provides the following technical solutions: One of the technical solutions of the present invention:

[0007] The present invention provides a method for preparing a stretchable flexible lithium-ion battery, wherein at least one of polystyrene-polybutadiene-polystyrene (SBS), polystyrene-polyisoprene-polystyrene (SIS), and polystyrene-polyethylene-polybutylene-polystyrene (SEBS) is used as a binder for positive electrode slurry and negative electrode slurry; and one of n-hexane, cyclohexane, and ethyl acetate is used as a solvent for the positive electrode slurry and the negative electrode slurry.

[0008] Furthermore, the method for preparing the stretchable flexible lithium-ion battery comprises the following steps:

[0009] Step 1: Mixing a PDMS (polydimethylsiloxane) prepolymer and a cross-linking agent, stirring them thoroughly to make them uniformly mixed, removing bubbles, obtaining a mixture, coating the mixture on a flexible substrate, and obtaining a PDMS film after drying;

[0010] Step 2: adding a binder into an organic solvent, heating and dissolving the binder to obtain a positive electrode precursor solution and a negative electrode precursor solution;

[0011] Step 3: mixing the positive electrode precursor solution, lithium iron phosphate and conductive carbon black, and stirring evenly to form a positive electrode slurry;

[0012] Step 4: mixing the negative electrode precursor solution, graphene and conductive carbon black, and stirring evenly to form a negative electrode slurry;

[0013] Step 5: coating silver paste on the surface of the PDMS film as positive and negative current collectors respectively, and drying to obtain a combination of a positive electrode region current collector, a negative electrode region current collector and a substrate material;

[0014] Step 6: coating the positive electrode slurry on the positive electrode current collector area, and obtaining a positive electrode sheet after drying; coating the negative electrode slurry on the negative electrode current collector area, and obtaining a negative electrode sheet after drying;

[0015] Step 7: In the positive electrode current collector area on the positive electrode sheet, an aluminum sheet tab is placed using silver paste as a binder, and the positive electrode is obtained after drying; in the negative electrode current collector area on the negative electrode sheet, a nickel sheet tab is placed using silver paste as a binder, and the negative electrode is obtained after drying, and the PDMS film is added at the connection between the positive and negative electrodes and the tabs as a fixing layer for connecting the tabs and the battery;

[0016] Step 8: dripping electrolyte solution between the positive and negative electrodes and on the surfaces of the positive and negative electrodes, covering the surfaces of the positive and negative electrodes with the PDMS film, and obtaining the stretchable flexible lithium-ion battery through sealing, standing, forming and volume separation;

[0017] There is no order of precedence between step 3 and step 4; there is no order of precedence between step 5 and step 6.

[0018] Aiming at the problem that the existing technology cannot complete the design of batteries of arbitrary shapes, and only part of the structure can be stretched or the stretchable battery array is adopted, and the individual batteries cannot be stretched. The present invention introduces elastic polymers (such as polystyrene-polybutadiene-polystyrene, polystyrene-polyisoprene-polystyrene, polystyrene-polyethylene-polybutylene-polystyrene) in the positive and negative electrode slurries for the first time, replacing the traditional polyvinylidene fluoride as a binder. This type of elastic polymer has both high elasticity and excellent mechanical properties, and can maintain the integrity of the internal structure and avoid cracking when subjected to tensile deformation. At the same time, its excellent electrochemical stability ensures that the battery performance is not affected during the charging and discharging process. Compared with traditional rigid binder materials, the high strain recovery ability of elastic polymers greatly improves the stretchability of the battery, so that the battery still maintains excellent conductivity and cycle life under multiple deformation conditions. Through systematic optimization, the present invention adopts flexible PDMS (polydimethylsiloxane) as the base material, and combines stretchable conductive silver paste as positive and negative current collectors to ensure the integrity of the overall structure of the battery under stretching conditions. The flexibility and elasticity of the PDMS substrate can effectively alleviate the damage to the electrode material caused by external forces, while the ductility and conductivity of the silver paste remain stable after multiple deformations. The overall stretchability of the battery is achieved through the high matching of the flexible current collector and the electrode material.

[0019] In the step 1, the mass ratio of the PDMS prepolymer to the cross-linking agent is 10:1; and / or

[0020] The bubble removal is to place the uniformly mixed PDMS prepolymer and the cross-linking agent into a vacuum drying oven for drying; and / or

[0021] The density of the mixture on the flexible substrate is 100-200 mg / m 2 , i.e. 100-200 mg of the mixture is uniformly coated per square meter of the flexible substrate; and / or

[0022] The drying temperature is 60-100°C.

[0023] Exemplarily, in step 1, the flexible substrate is a polymer substrate such as polyvinyl chloride (PVC) or polyethylene terephthalate (PET).

[0024] In the step 2, the mass ratio of the binder to the solvent is (1-3): (40-60); and / or

[0025] The heating temperature is 40-60° C., and the heating and dissolving is carried out under stirring conditions. The preferred heating method is water bath heating. The heating and dissolving is preferably carried out in a water bath pot with a rotor, and the stirring speed of the rotor is 1000-1500 rpm.

[0026] In the step 3, the mass ratio of the positive electrode precursor solution to lithium iron phosphate and conductive carbon black is (80-160):(12-20):(1-3).

[0027] In step 3, lithium iron phosphate is used as the positive electrode active material, and conductive carbon black is used as the conductive additive.

[0028] In the step 4, the mass ratio of the negative electrode precursor solution to graphene and conductive carbon black is (80-160):(12-20):(1-3).

[0029] In step 4, graphene is used as the negative electrode active material, and conductive carbon black is used as the conductive additive.

[0030] In step 5, the coating thickness of the silver paste is 0.05-0.1 mm; the coating speed is 10-20 mm / s; and / or

[0031] The drying temperature is 100-140° C. and the drying time is 30-50 minutes.

[0032] Exemplarily, in step 5, the silver paste has a viscosity of 15-25 pa.s and a solid content of 57-67%.

[0033] In step 6, the coating thickness of the positive electrode slurry is 0.05 mm-0.1 mm, and the coating speed is 10-20 mm / s; and / or

[0034] The coating thickness of the negative electrode slurry is 0.05 mm-0.1 mm, and the coating speed is 10-20 mm / s.

[0035] Exemplarily, in step 6, the drying temperature is 45-60°C.

[0036] In step 7, the width of the aluminum sheet tab is 3-6 mm and the thickness is 0.05-0.15 mm; and / or

[0037] The nickel sheet tab has a width of 3-6 mm and a thickness of 0.05-0.15 mm.

[0038] Exemplarily, in step 7, the drying temperature is 45-60°C.

[0039] In step 8, the density of the electrolyte solution is 1.2-1.3 g / cc, the lithium salt of the electrolyte solution is LiPF6, the mass fraction of the lithium salt in the electrolyte solution is 10-15 wt.%, and the solvent of the electrolyte solution is a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 1:1:1.

[0040] The second technical solution of the present invention:

[0041] The present invention also provides a stretchable flexible lithium-ion battery prepared according to the above method.

[0042] The stretchable flexible lithium-ion battery of the present invention can also be charged and discharged when stretched, and wearable electronic devices can be designed according to the stretching requirements of different parts to cope with more complex human body environments.

[0043] Compared with the prior art, the present invention has the following advantages and technical effects:

[0044] The present invention prepares an electrode precursor solution by adding at least one of polystyrene-polybutadiene-polystyrene (SBS), polystyrene-polyisoprene-polystyrene (SIS), and polystyrene-polyethylene-polybutylene-polystyrene (SEBS) as a binder, and one of n-hexane, cyclohexane, and ethyl acetate as a binder solvent, and uses conductive carbon black as a conductive material, lithium iron phosphate as a positive electrode, and graphene as a negative electrode to prepare stretchable positive and negative electrodes respectively. Compared with the existing method using polyvinylidene fluoride as a binder, N-methylpyrrolidone as a binder solvent, conductive carbon black as a conductive material, lithium iron phosphate as a positive electrode, and graphene as a negative electrode, the stretchability of the positive and negative electrodes is improved while ensuring that the specific capacity is similar to that of the prior art. The present invention uses stretchable conductive silver paste as a current collector, replacing traditional aluminum foil as a positive current collector and copper foil as a negative current collector, thereby improving the stretchability of the current collector. The present invention uses a stretchable PDMS substrate, a current collector, and positive and negative electrodes to provide a design scheme for stretchable full battery materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0046] Figure 1 Schematic diagram of the structure of a stretchable flexible lithium-ion battery prepared in an embodiment of the present invention, wherein: 1-polyvinyl chloride substrate, 2-PDMS film substrate, 3-PDMS film covering layer, 4-aluminum sheet positive electrode tab, 5-nickel sheet negative electrode tab, 6-silver paste layer, 7-positive electrode, 8-negative electrode, 9-electrolyte;

[0047] Figure 2 A photograph of the combination of the positive electrode region current collector, the negative electrode region current collector and the substrate material prepared in Example 1;

[0048] Figure 3 The photographs of the positive electrode coated with the positive electrode slurry and the negative electrode coated with the negative electrode slurry prepared in Example 1;

[0049] Figure 4 This is a front view of the stretchable flexible lithium-ion battery after packaging in Example 1;

[0050] Figure 5 This is a comparison diagram of the stretchable flexible lithium-ion battery in Example 2 after longitudinal stretching by 20%, the left diagram is before stretching, and the right diagram is after stretching;

[0051] Figure 6 This is a comparison diagram of the stretchable flexible lithium-ion battery after transverse stretching in Example 2, the left diagram is before stretching, and the right diagram is after stretching;

[0052] Figure 7 This is a diagram of the U-shaped current collector mold used in Example 4;

[0053] Figure 8 This is a diagram of the U-shaped positive electrode mold used in Example 4;

[0054] Fig. 9 Schematic diagram of the structure of the stretchable flexible lithium-ion battery in Example 4, wherein: 1-polyvinyl chloride substrate, 2-PDMS film substrate, 3-PDMS film covering layer, 4-aluminum sheet positive electrode tab, 5-nickel sheet negative electrode tab, 6-silver paste layer, 7-positive electrode, 8-negative electrode, 9-electrolyte;

[0055] Fig.10 This is a comparison diagram of the stretchable flexible lithium-ion battery after stretching in Example 4, the left diagram is before stretching, and the right diagram is after stretching;

[0056] Fig.11 It is a schematic diagram of the structure of a spiral stretchable flexible lithium-ion battery, wherein: 1-polyvinyl chloride substrate, 2-PDMS film substrate, 3-PDMS film covering layer, 4-aluminum sheet positive electrode tab, 5-nickel sheet negative electrode tab, 6-silver paste layer, 7-positive electrode, 8-negative electrode, 9-electrolyte. DETAILED DESCRIPTION

[0057] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0058] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0059] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0060] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0061] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0062] In some embodiments of the present invention, a method for preparing a stretchable flexible lithium-ion battery is provided, comprising the following steps:

[0063] Step 1: Mix the PDMS prepolymer and the crosslinking agent, stir them thoroughly to make them evenly mixed, put them into a vacuum drying oven to remove bubbles, obtain a mixture, apply the mixture on a polyvinyl chloride substrate, and obtain a PDMS film after drying, wherein the mass ratio of the PDMS prepolymer to the crosslinking agent is 10:1, and the density of the mixture on the polyvinyl chloride substrate is 100-200 mg / m 2 , that is, 100-200 mg of the mixture is evenly coated on each square meter of the polyvinyl chloride board, and the drying temperature is 60-100°C;

[0064] Step 2: adding a binder to an organic solvent, heating and dissolving, to obtain a positive electrode precursor solution and a negative electrode precursor solution, wherein the binder comprises at least one of polystyrene-polybutadiene-polystyrene (SBS), polystyrene-polyisoprene-polystyrene (SIS), and polystyrene-polyethylene-polybutylene-polystyrene (SEBS); the solvent comprises one of n-hexane, cyclohexane, and ethyl acetate; the mass ratio of the binder to the solvent is (1-3): (40-60); the heating temperature is 40-60° C., and the heating and dissolution are carried out under stirring conditions, preferably the heating method is water bath heating, and preferably the heating and dissolution is carried out in a water bath pot with a rotor, and the stirring speed of the rotor is 1000-1500 rpm; the flexible substrate is a polymer substrate such as polyvinyl chloride (PVC) and polyethylene terephthalate (PET);

[0065] Step 3: mixing the positive electrode precursor solution, lithium iron phosphate and conductive carbon black, and stirring them evenly to form a positive electrode slurry, wherein the mass ratio of the positive electrode precursor solution, lithium iron phosphate and conductive carbon black is (80-160): (12-20): (1-3);

[0066] Step 4: mixing the negative electrode precursor solution, graphene and conductive carbon black, and stirring them evenly to form a negative electrode slurry, wherein the mass ratio of the negative electrode precursor solution, graphene and conductive carbon black is (80-160): (12-20): (1-3);

[0067] Step 5: coating silver paste on the surface of the PDMS film (i.e., the PDMS film substrate) as positive and negative current collectors respectively, and drying to obtain a combination of a positive electrode region current collector, a negative electrode region current collector and a substrate material, wherein graphene is a negative electrode active material and conductive carbon black is a conductive additive; the coating thickness of the silver paste is 0.05-0.1 mm; the coating speed is 10-20 mm / s; the drying temperature is 100-140° C., and the time is 30-50 min; the viscosity of the silver paste is 15-25 pa.s, and the solid content is 57-67%;

[0068] Step 6: coating the positive electrode slurry on the positive electrode current collector area, and obtaining a positive electrode sheet after drying; coating the negative electrode slurry on the negative electrode current collector area, and obtaining a negative electrode sheet after drying, wherein the coating thickness of the positive electrode slurry is 0.05mm-0.1mm, and the coating speed is 10-20mm / s; the coating thickness of the negative electrode slurry is 0.05mm-0.1mm, and the coating speed is 10-20mm / s; the drying temperature is 45-60°C;

[0069] Step 7: In the positive electrode current collector area on the positive electrode sheet, an aluminum sheet pole ear is placed using silver paste as a binder, and a positive electrode is obtained after drying; in the negative electrode current collector area on the negative electrode sheet, a nickel sheet pole ear is placed using silver paste as a binder, and a negative electrode is obtained after drying, and the PDMS film is added at the connection between the positive and negative electrodes and the pole ear as a fixing layer for connecting the pole ear and the battery, wherein the width of the aluminum sheet pole ear is 3-6 mm and the thickness is 0.05-0.15 mm; the width of the nickel sheet pole ear is 3-6 mm and the thickness is 0.05-0.15 mm, and the drying temperature is 45-60°C;

[0070] Step 8: dripping electrolyte solution between the positive and negative electrodes and on the surfaces of the positive and negative electrodes, covering the surfaces of the positive and negative electrodes with the PDMS film (i.e., the PDMS film covering layer), and obtaining a stretchable flexible lithium-ion battery by sealing, standing, forming, and volume separation, wherein the density of the electrolyte solution is 1.2-1.3 g / cc, the lithium salt of the electrolyte solution is LiPF6, the mass fraction of the lithium salt in the electrolyte solution is 10-15 wt%, and the solvent of the electrolyte solution is a mixture of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a mass ratio of 1:1:1;

[0071] There is no order of precedence for step 3 and step 4; there is no order of precedence for step 5 and step 6.

[0072] In some embodiments of the present invention, mold printing is used to prepare positive and negative electrodes. Both the positive electrode mold and the negative electrode mold are SMT laser templates with a thickness of 80μm-200μm. The shape of the positive electrode mold and the negative electrode mold can be one of a line segment shape, a U shape, a cross-finger shape and a spiral shape. The hollow area in the positive electrode mold is the effective area for coating the positive electrode slurry, and the coating area is greater than or equal to the negative electrode effective area. The area of ​​a single electrode in the positive electrode mold and the negative electrode mold is independently 30μm 2 -3cm 2 , the preferred range is 3mm 2 -1cm 2 ; The width of the electrode is 2mm-4mm.

[0073] In a typical embodiment of the present invention, the density of the electrolyte solution is 1.3 g / cc, the lithium salt of the electrolyte solution is LiPF6, the mass fraction of the lithium salt in the electrolyte solution is 15 wt%, and the solvent of the electrolyte solution is a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 1:1:1.

[0074] The present invention uses a stretchable conductive silver paste as a current collector, replacing the traditional carbon cloth as a current collector, thereby improving the stretchability of the current collector. The present invention uses a stretchable PDMS substrate, a current collector, and positive and negative electrodes to provide a stretchable design scheme for the entire battery material, which is sufficient to ensure that the battery can be charged and discharged normally when stretched by 20%.

[0075] Unless otherwise specified, the normal temperature in the examples and comparative examples of the present invention is 25±2°C.

[0076] All raw materials used in the examples and comparative examples of the present invention are purchased from commercial sources.

[0077] Dow Corning SYLGARD184 silicone rubber is a two-component kit product composed of liquid components, including 1kg of basic components and 100g of curing agent. The basic components and curing agent are completely mixed in a weight ratio of 10:1. The consistency of the medium-viscosity mixed liquid is similar to that of SAE40 engine oil (model: 184, brand: Dow Corning, origin: the United States, ingredients: PDMS and curing agent, mixing ratio: 10:1, mass ratio). Regardless of thickness, the mixed liquid will cure into a tough transparent elastomer suitable for electronic / electrical packaging and potting applications. Dow Corning SYLGARD184 silicone rubber cures in the temperature range of 25℃ to 150℃, without exothermic phenomenon, and no secondary curing is required. After the curing process is completed, it can be used immediately in the temperature range of -55℃ to 200℃. As an example, in the embodiments of the present invention and the comparative examples, the PDMS prepolymer is the basic component of Dow Corning SYLGARD-184 silicone rubber; the cross-linking agent used is the curing agent in Dow Corning SYLGARD-184 silicone rubber; polystyrene-polyisoprene-polystyrene, polystyrene-polybutadiene-polystyrene and polystyrene-polyethylene-polybutylene-polystyrene are all purchased from Aladdin; the silver paste is the EL-8622 series stretchable conductive silver paste purchased from Xin Shuangbang Technology Co., Ltd., with a silver paste viscosity of 20 Pa.s and a solid content of 62%; lithium iron phosphate is purchased from Aladdin, with a particle size of <5 μm and a purity of >97%.

[0078] In the embodiments of the present invention, "first efficiency" refers to the first efficiency of the battery, which describes the ratio of the capacity released by the lithium-ion battery during discharge after the first charge to the capacity charged during the first charge. This ratio is usually less than 1, because some lithium ions will be irreversibly lost during the first charge, mainly due to the formation of a stable solid electrolyte interface film (SEI film) on the surface of the negative electrode. The first efficiency is an important parameter to measure the actual degree of lithium insertion and the actual released capacity of the battery material. The higher the first efficiency, the less irreversible lithium loss and consumption during the positive electrode film formation process, which means a high recoverable capacity.

[0079] The structural schematic diagram of the stretchable flexible lithium-ion battery in Examples 1 to 3 of the present invention is shown in Figure 1 , wherein: 1-polyvinyl chloride substrate, 2-PDMS film substrate, 3-PDMS film covering layer, 4-aluminum sheet positive electrode tab, 5-nickel sheet negative electrode tab, 6-silver paste layer, 7-positive electrode, 8-negative electrode, 9-electrolyte.

[0080] It should be pointed out that the matters not described in detail in the present invention are all conventional operating means in the field and are not the focus of the present invention. For example, specific methods such as sealing, standing, forming, and volume separation are all completed by conventional methods.

[0081] The technical solution of the present invention is further illustrated by the following embodiments.

[0082] Example 1

[0083] This embodiment provides a stretchable flexible lithium-ion battery and a preparation method:

[0084] Step 1: Mix 7g of PDMS prepolymer and 0.7g of cross-linking agent, stir them thoroughly to make them evenly mixed, put them into a vacuum drying oven at room temperature to remove bubbles (the vacuum degree of the vacuum drying oven is 5kPa), and obtain a mixture, which is coated on a polyvinyl chloride substrate (the density of the mixture is 100mg / m 2 , i.e., 100 mg of the mixture is uniformly coated on each square meter of the polyvinyl chloride substrate), and then placed in an oven (the oven temperature is 60°C) and dried for 4 hours to obtain a PDMS film;

[0085] Step 2: Add 0.1 g of polystyrene-polyisoprene-polystyrene (styrene mass percentage is 22%) to 2.6 g of n-hexane, heat in a water bath at 50°C to dissolve (water bath heating is carried out in a water bath with a rotor, the same below), and the rotor stirring speed is 1000 rpm to obtain a positive electrode precursor solution; add 0.1 g of polystyrene-polyisoprene-polystyrene (styrene 22 wt.%) to 2.6 g of n-hexane, heat in a water bath at 50°C to dissolve, and the rotor stirring speed is 1000 rpm to obtain a negative electrode precursor solution;

[0086] Step 3: 2.7 g of positive electrode precursor solution, lithium iron phosphate and conductive carbon black were mixed in a mass ratio of 2.7:0.4:0.05, and stirred evenly to form a positive electrode slurry;

[0087] Step 4: 2.7 g of negative electrode precursor solution, graphene and conductive carbon black were mixed in a mass ratio of 2.7:0.4:0.05, and stirred evenly to form a negative electrode slurry;

[0088] Step 5: Coat two pieces of silver paste with a thickness of 80 μm, a length of 30 mm, and a width of 3 mm on the surface of the PDMS film obtained in step 1 as positive and negative current collectors respectively, put them into an oven for baking and drying for 40 minutes at an oven temperature of 150°C to obtain a combination of a positive electrode region current collector, a negative electrode region current collector, and a substrate material;

[0089] Step 6: Apply the positive electrode slurry to the positive electrode collector area, using an 80μm four-sided preparation device for coating. The coated positive electrode slurry has a thickness of 80μm, a length of 25mm, a width of 3mm, and a coating speed of 10mm / s; after oven drying, the oven temperature is 50°C to obtain a positive electrode sheet. Apply the negative electrode slurry to the negative electrode collector area, using an 80μm four-sided preparation device for coating. The coated negative electrode slurry has a thickness of 80μm, a length of 25mm, a width of 3mm, and a coating speed of 10mm / s; after oven drying, the oven temperature is 50°C to obtain a negative electrode sheet;

[0090] Step 7: In the positive electrode current collector area, use silver paste as a binder to place an aluminum sheet tab with a width of 3 mm and a thickness of 0.1 mm; in the negative electrode current collector area, use silver paste as a binder to place a nickel sheet tab with a width of 3 mm and a thickness of 0.1 mm, put it in an oven for drying (the oven temperature is 45°C), and after drying, add a PDMS film (the preparation method of the PDMS film is the same as step 1) at the connection between the positive and negative electrodes and the tab as a fixing layer for connecting the tab and the battery;

[0091] Step 8: drip an electrolyte solution between the positive and negative electrodes and on the surfaces of the positive and negative electrodes, wherein the density of the electrolyte solution is 1.3 g / cc, the lithium salt of the electrolyte solution is LiPF6, the mass fraction of the lithium salt in the electrolyte solution is 15 wt%, and the solvent of the electrolyte solution is a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 1:1:1; after dripping the electrolyte solution, ensure that the surface of the positive and negative electrodes is wetted; cover the surface with a PDMS film (the preparation method of the PDMS film is the same as that of step 1), and obtain a stretchable flexible lithium-ion battery by sealing, standing, forming, and dividing the volume.

[0092] The photo of the combination of the positive electrode region current collector, the negative electrode region current collector and the substrate material prepared in Example 1 is shown in Figure 2 The photo of the positive electrode coated with the positive electrode slurry prepared in Example 1 and the photo of the negative electrode coated with the negative electrode slurry are shown in Figure 3 The front view of the stretchable flexible lithium-ion battery after packaging in Example 1 is shown in Figure 4 It can be observed that the overall surface of the battery is flat, the slurry layer is well bonded to the substrate, and no obvious cracks or delamination are observed. This shows that the combination of flexible silver paste and elastic polymer gives the coating good adhesion and flexibility.

[0093] Example 2

[0094] This embodiment provides a stretchable flexible lithium-ion battery and a preparation method:

[0095] Step 1: Mix 7g of PDMS prepolymer with 0.7g of cross-linking agent, stir thoroughly to make the mixture uniform, put it into a vacuum drying oven at room temperature to remove bubbles (the vacuum degree of the vacuum drying oven is 5kPa), and obtain a mixture, which is coated on a polyvinyl chloride substrate (the density of the mixture is 200mg / m 2 ), put it into an oven (oven temperature is 60°C) and dry it for 4 hours to obtain a PDMS film;

[0096] Step 2: Add 0.2 g of polystyrene-polyisoprene-polystyrene (styrene 17 wt.%) to 3 g of cyclohexane, heat to dissolve in a water bath at 50°C, and stir the rotor at a speed of 1500 rpm to obtain a positive electrode precursor solution; add 0.2 g of polystyrene-polyisoprene-polystyrene (styrene 17 wt.%) to 3 g of n-hexane, heat to dissolve in a water bath at 50°C, and stir the rotor at a speed of 1000 rpm to obtain a negative electrode precursor solution;

[0097] Step 3: 3.2 g of the positive electrode precursor solution, lithium iron phosphate and conductive carbon black were mixed in a mass ratio of 3.2:0.35:0.05, and stirred to form a positive electrode slurry;

[0098] Step 4: 3.2 g of negative electrode precursor solution, graphene and conductive carbon black were mixed in a mass ratio of 3.2:0.35:0.05, and stirred to form a negative electrode slurry;

[0099] Step 5: Coat two pieces of silver paste with a thickness of 80 μm, a length of 30 mm, and a width of 3 mm on the surface of the PDMS film obtained in step 1 as positive and negative current collectors respectively, put them into an oven for baking and drying for 40 minutes at an oven temperature of 150°C to obtain a combination of a positive electrode region current collector, a negative electrode region current collector, and a substrate material;

[0100] Step 6: Apply the positive electrode slurry to the positive electrode collector area, using an 80μm four-sided preparation device for coating. The coated positive electrode slurry has a thickness of 80μm, a length of 25mm, a width of 3mm, and a coating speed of 10mm / s; after oven drying, the oven temperature is 50°C to obtain a positive electrode sheet. Apply the negative electrode slurry to the negative electrode collector area, using an 80μm four-sided preparation device for coating. The coated negative electrode slurry has a thickness of 80μm, a length of 25mm, a width of 3mm, and a coating speed of 10mm / s; after oven drying, the oven temperature is 50°C to obtain a negative electrode sheet;

[0101] Step 7: In the positive current collector area, use silver paste as a binder to place aluminum tabs with a width of 4mm and a thickness of 0.1mm; in the negative current collector area, use silver paste as a binder to place nickel tabs with a width of 4mm and a thickness of 0.1mm, and put them in an oven to dry. After drying, add PDMS film (the preparation method of PDMS film is the same as step 1) at the connection between the positive and negative electrodes and the tabs as a fixing layer connecting the tabs and the battery;

[0102] Step 8: drip an electrolyte solution between the positive and negative electrodes and on the surfaces of the positive and negative electrodes, wherein the density of the electrolyte solution is 1.3 g / cc, the lithium salt of the electrolyte solution is LiPF6, and the mass fraction of the lithium salt in the electrolyte solution is 15wt%. The solvent of the electrolyte solution is a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 1:1:1. After dripping the electrolyte solution, ensure that the surface of the positive and negative electrodes is wetted; cover the surface with a PDMS film (the preparation method of the PDMS film is the same as that of step 1), and obtain a stretchable flexible lithium-ion battery by sealing, standing, forming, and dividing the capacity.

[0103] The comparison diagram of the stretchable flexible lithium-ion battery in Example 2 after longitudinal stretching by 20% is shown in Figure 5 , the comparison diagram of the stretchable flexible lithium-ion battery after transverse stretching in Example 2 is shown in Figure 6 It can be seen that under the condition of 20% longitudinal and transverse stretching, there are no obvious cracks on the battery surface, and the current collector and electrode slurry still maintain good consistency. This shows that the positive and negative electrodes with PDMS substrate and elastic polymer as binder have excellent deformation adaptability in multi-axial stretching, and the slurry delamination and peeling phenomenon is effectively suppressed during the stretching process.

[0104] Example 3

[0105] This embodiment provides a stretchable flexible lithium-ion battery and a preparation method:

[0106] Step 1: Mix 10g of PDMS prepolymer with 1g of cross-linking agent, stir thoroughly to make the mixture uniform, put it in a vacuum drying oven at room temperature for 1h to remove bubbles (the oven temperature is 100°C), and then coat the mixture on a PET substrate (the density of the mixture is 100mg / m 2 ), put it into an oven to obtain a PDMS film;

[0107] Step 2: Add 0.1 g of polystyrene-polyisoprene-polystyrene and 0.1 g of polystyrene-polyethylene-polybutylene-polystyrene to 2.5 g of ethyl acetate, heat in a water bath at 50° C. to dissolve, and obtain a positive electrode precursor solution; add 0.1 g of polystyrene-polybutadiene-polystyrene (styrene 30 wt.%) and 0.1 g of polystyrene-polyethylene-polybutylene-polystyrene to 2.5 g of ethyl acetate, heat in a water bath at 45° C. to dissolve, and obtain a negative electrode precursor solution;

[0108] Step 3: 2.7 g of positive electrode precursor solution, lithium iron phosphate and conductive carbon black were mixed in a mass ratio of 2.7:0.4:0.05, and stirred to form a positive electrode slurry;

[0109] Step 4: 2.7 g of negative electrode precursor solution, graphene and conductive carbon black were mixed in a mass ratio of 2.7:0.4:0.05, and stirred to form a negative electrode slurry;

[0110] Step 5: Coat two pieces of silver paste with a thickness of 80 μm on the surface of the PDMS film prepared in step 1 as positive and negative current collectors respectively, put them into an oven and bake them for 40 minutes at a temperature of 150° C. to obtain a combination of a positive electrode region current collector, a negative electrode region current collector and a substrate material;

[0111] Step 6: Coat the positive electrode slurry on the positive electrode current collector area using a four-sided preparation device with a length of 80 μm, a width of 30 mm, and a coating speed of 10 mm / s; dry in an oven at a temperature of 50°C to obtain a positive electrode sheet;

[0112] The negative electrode slurry is coated on the negative electrode current collector area, and an 80 μm four-sided coating device is used for coating. The coated negative electrode slurry has a thickness of 80 μm, a length of 25 mm, a width of 3 mm, and a coating speed of 10 mm / s; after drying in an oven at a temperature of 45° C., a negative electrode sheet is obtained;

[0113] Step 7: In the positive electrode current collector area, use silver paste as a binder to place an aluminum tab with a width of 3mm and a thickness of 0.1mm; in the negative electrode current collector area, use silver paste as a binder to place a nickel tab with a width of 3mm and a thickness of 0.1mm, and put it in an oven to dry. After drying, add a PDMS film (the preparation method of the PDMS film is the same as step 1) at the connection between the positive and negative electrodes and the tabs as a fixing layer connecting the tabs and the battery;

[0114] Step 8: drip an electrolyte solution between the positive and negative electrodes and on the surfaces of the positive and negative electrodes, wherein the density of the electrolyte solution is 1.3 g / cc, the lithium salt of the electrolyte solution is LiPF6, the mass fraction of the lithium salt in the electrolyte solution is 15 wt%, and the solvent of the electrolyte solution is a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 1:1:1; after dripping the electrolyte solution, ensure that the surface of the positive and negative electrodes is wetted; cover the surface with a PDMS film (the preparation method of the PDMS film is the same as that of step 1), and obtain a stretchable flexible lithium-ion battery by sealing, standing, forming, and dividing the volume.

[0115] Example 4

[0116] This embodiment provides a stretchable flexible lithium-ion battery and a preparation method:

[0117] Step 1: Mix 7g of PDMS prepolymer and 0.7g of cross-linking agent, stir them thoroughly to make them evenly mixed, put them into a vacuum drying oven at room temperature to remove bubbles (the vacuum degree of the vacuum drying oven is 5kPa), and obtain a mixture, which is coated on a polyvinyl chloride substrate (the density of the mixture is 100mg / m 2 , i.e., 100 mg of the mixture is uniformly coated on each square meter of the polyvinyl chloride substrate), and then placed in an oven (the oven temperature is 60°C) and dried for 4 hours to obtain a PDMS film;

[0118] Step 2: Add 0.1 g of polystyrene-polyisoprene-polystyrene (22 wt. %) of styrene to 2.6 g of n-hexane, heat in a water bath at 50°C to dissolve (water bath heating is carried out in a water bath with a rotor, the same below), and the rotor stirring speed is 1000 rpm to obtain a positive electrode precursor solution; add 0.1 g of polystyrene-polyisoprene-polystyrene (22 wt. %) of styrene to 2.6 g of n-hexane, heat in a water bath at 50°C to dissolve, and the rotor stirring speed is 1000 rpm to obtain a negative electrode precursor solution;

[0119] Step 3: 2.7 g of positive electrode precursor solution, lithium iron phosphate and conductive carbon black were mixed in a mass ratio of 2.7:0.4:0.05, and stirred evenly to form a positive electrode slurry;

[0120] Step 4: 2.7 g of negative electrode precursor solution, graphene and conductive carbon black were mixed in a mass ratio of 2.7:0.4:0.05, and stirred evenly to form a negative electrode slurry;

[0121] Step 5: Coat two U-shaped silver pastes on the surface of the PDMS film obtained in step 1 as positive and negative current collectors (see the U-shaped current collector mold used in the figure). Figure 7The length of the left side of the U-shaped area is 31.5mm, the length of the right side is 27mm, the width is 27mm, the width is 3mm, the interval between the two U-shaped areas is 1.5mm, and the total area is 436.5mm 2 ) put into an oven for baking and drying for 40 minutes, the oven temperature is 120° C., to obtain a combination of a positive electrode region current collector, a negative electrode region current collector and a substrate material;

[0122] Step 6: Coat the positive electrode slurry on the positive electrode current collector area using an 80 μm four-sided preparation device. The coated positive electrode slurry has a thickness of 80 μm and a width of 3 mm. The coating area is U-shaped and the coating speed is 10 mm / s. After drying in an oven at 50 ° C, a positive electrode sheet is obtained (see the U-shaped positive electrode mold used). Figure 8 ). The negative electrode slurry is coated on the negative electrode current collector area, and an 80 μm four-sided preparation device is used for coating. The thickness of the coated negative electrode slurry is 80 μm, the width is 3 mm, the coating area is U-shaped, the coating speed is 10 mm / s, and the negative electrode sheet is obtained after drying in an oven at a temperature of 50°C;

[0123] Step 7: In the positive electrode current collector area, use silver paste as a binder to place an aluminum sheet tab with a width of 3 mm and a thickness of 0.1 mm; in the negative electrode current collector area, use silver paste as a binder to place a nickel sheet tab with a width of 3 mm and a thickness of 0.1 mm, put it in an oven for drying (the oven temperature is 45°C), and after drying, add a PDMS film (the preparation method of the PDMS film is the same as step 1) at the connection between the positive and negative electrodes and the tab as a fixing layer for connecting the tab and the battery;

[0124] Step 8: drip an electrolyte solution between the positive and negative electrodes and on the surfaces of the positive and negative electrodes, wherein the density of the electrolyte solution is 1.2 g / cc, the lithium salt of the electrolyte solution is LiPF6, the mass fraction of the lithium salt in the electrolyte solution is 12 wt%, and the solvent of the electrolyte solution is a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 1:1:1; after dripping the electrolyte solution, ensure that the surface of the positive and negative electrodes is wetted; cover the surface with a PDMS film (the preparation method of the PDMS film is the same as that of step 1), and obtain a stretchable flexible lithium-ion battery by sealing, standing, forming, and dividing the capacity.

[0125] The structural schematic diagram of the stretchable flexible lithium-ion battery in this embodiment is shown in Fig. 9 , wherein: 1-polyvinyl chloride substrate, 2-PDMS film substrate, 3-PDMS film covering layer, 4-aluminum sheet positive electrode tab, 5-nickel sheet negative electrode tab, 6-silver paste layer, 7-positive electrode, 8-negative electrode, 9-electrolyte.

[0126] The comparison diagram of the stretchable flexible lithium-ion battery after stretching in this embodiment is shown in Fig.10It can be seen that in the battery structure after stretching, there are no cracks in the U-shaped area, and the interface between the slurry and the silver paste layer is stable, indicating that the multi-morphological design also has excellent deformation adaptability.

[0127] By using the same method as in Example 4 and replacing molds of different shapes, flexible batteries of different shapes can be obtained. Fig.11 .

[0128] Comparative Example 1

[0129] Step 1: Mix 7g of PDMS prepolymer with 0.7g of cross-linking agent, stir thoroughly to make the mixture uniform, put it into a vacuum drying oven at room temperature to remove bubbles (the vacuum degree of the vacuum drying oven is 5kPa), and obtain a mixture, which is coated on a polyvinyl chloride substrate (the density of the mixture is 100mg / m 2 ), put it into an oven (oven temperature is 60°C) and dry it for 4 hours to obtain a PDMS film;

[0130] Step 2: 0.8 g of lithium iron phosphate, conductive carbon black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and then 4 g of N-methylpyrrolidone was added and stirred to form a positive electrode slurry, wherein the lithium iron phosphate was purchased from Aladdin, with a particle size of <5 μm and a purity of more than 97%;

[0131] Step 4: 0.8 g of graphene, conductive carbon black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and then 4 g of N-methylpyrrolidone was added and stirred to form a negative electrode slurry;

[0132] Step 5: Coat two pieces of silver paste with a thickness of 80 μm, a length of 30 mm, and a width of 3 mm on the surface of the PDMS film prepared in step 1 as positive and negative current collectors respectively, put them into an oven for baking and drying for 40 minutes, and the oven temperature is 150°C to obtain a combination of a positive electrode region current collector, a negative electrode region current collector, and a substrate material, wherein the silver paste is the EL-8622 series stretchable conductive silver paste purchased from Xin Shuangbang Technology Co., Ltd., the silver paste viscosity is 20 pa.s, and the solid content is 62%;

[0133] Step 6: Coat the positive electrode slurry on the positive electrode collector area, use an 80μm four-sided preparation device for coating, the coated positive electrode slurry has a thickness of 80μm, a length of 25mm, a width of 3mm, and a coating speed of 10mm / s; after oven drying, the oven temperature is 50°C to obtain a positive electrode sheet; Coat the negative electrode slurry on the negative electrode collector area, use an 80μm four-sided preparation device for coating, the coated negative electrode slurry has a thickness of 80μm, a length of 25mm, a width of 3mm, and a coating speed of 10mm / s; after oven drying, the oven temperature is 50°C to obtain a negative electrode sheet;

[0134] Step 7: In the positive electrode current collector area, use silver paste as a binder to place an aluminum sheet tab with a width of 3 mm and a thickness of 0.1 mm; in the negative electrode current collector area, use silver paste as a binder to place a nickel sheet tab with a width of 3 mm and a thickness of 0.1 mm, put it in an oven for drying, the oven temperature is 45°C, and after drying, add a PDMS film (the preparation method of the PDMS film is the same as step 1) at the connection between the positive and negative electrodes and the tab as a fixing layer for connecting the tab and the battery;

[0135] Step 8: drip an electrolyte solution between the positive and negative electrodes and on the surfaces of the positive and negative electrodes, wherein the density of the electrolyte solution is 1.3 g / cc, the lithium salt of the electrolyte solution is LiPF6, the mass fraction of the lithium salt in the electrolyte solution is 15wt%, and the solvent of the electrolyte solution is a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 1:1:1; after dripping the electrolyte solution, ensure that the surfaces of the positive and negative electrodes are wetted; cover the surfaces with a PDMS film (the preparation method of the PDMS film is the same as that of step 1), and obtain a lithium-ion battery by sealing, standing, forming, and dividing the capacity.

[0136] The performance test of the flexible stretchable battery prepared in the above embodiment is carried out, and the test method involved is: using a Xinwei tester to measure the charge and discharge performance, the charge rate is 0.1C, the discharge rate is 0.2C, and the cut-off voltage is 3.0-4.4V.

[0137] The test results of flexible stretchable battery performance are shown in Table 1.

[0138] Table 1 Flexible stretchable battery performance test results

[0139]

[0140] It can be seen from the data in Table 1 that the flexible stretchable batteries of Examples 1 to 3 have higher specific capacity, coulombic efficiency and charge-discharge performance, and the appropriate coating process ensures the flexibility of the positive and negative electrodes and the stability of the coating layer, and the coating layer will not crack or fall off during use. In the unstretched state, the data of Examples 1 to 3 and Comparative Example 1 are close, and the specific capacity, coulombic efficiency and charge-discharge performance of the flexible stretchable battery of the present invention are similar to those of the lithium-ion battery prepared by the existing method.

[0141] The lithium ion batteries prepared in Example 1 and Comparative Example 1 were respectively stretched by 0%, 10%, and 20% for charge and discharge tests (the test methods are the same as above). The results are shown in Table 2.

[0142] Table 2 Performance test results of flexible stretchable batteries after stretching

[0143]

[0144] It can be seen from the data in Table 2 that the lithium-ion battery of Example 1 can still be charged and discharged normally after stretching. When the lithium-ion battery of Comparative Example 1 is stretched by 10%, the specific capacity and charge-discharge capacity are lower than those of Example 1, and it cannot be charged normally when stretched by 20%. The elastic polymer added to the positive and negative electrode slurries of Example 1 replaces the polyvinylidene fluoride in Comparative Example 1, which improves the stretchability of the battery. The positive and negative electrode slurries and the battery assembly method can ensure that the battery can be charged and discharged normally when stretched by 20%. In summary, the preparation method of the present invention can be used to prepare flexible batteries with various shape requirements.

[0145] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a stretchable flexible lithium-ion battery, characterized in that: At least one of polystyrene-polybutadiene-polystyrene, polystyrene-polyisoprene-polystyrene and polystyrene-polyethylene-polybutylene-polystyrene is used as a binder for the positive electrode slurry and the negative electrode slurry; one of n-hexane, cyclohexane and ethyl acetate is used as a solvent for the positive electrode slurry and the negative electrode slurry.

2. The method for preparing a stretchable flexible lithium-ion battery according to claim 1, characterized in that: The following steps are involved: Step 1: Mix the PDMS prepolymer and the cross-linking agent, stir them thoroughly to make them evenly mixed, remove bubbles, obtain a mixture, apply the mixture on a flexible substrate, and obtain a PDMS film after drying; Step 2: adding a binder into an organic solvent, heating and dissolving the binder to obtain a positive electrode precursor solution and a negative electrode precursor solution; Step 3: mixing the positive electrode precursor solution, lithium iron phosphate and conductive carbon black, and stirring evenly to form a positive electrode slurry; Step 4: mixing the negative electrode precursor solution, graphene and conductive carbon black, and stirring evenly to form a negative electrode slurry; Step 5: coating silver paste on the surface of the PDMS film as positive and negative current collectors respectively, and drying to obtain a combination of a positive electrode region current collector, a negative electrode region current collector and a substrate material; Step 6: coating the positive electrode slurry on the positive electrode current collector area, and obtaining a positive electrode sheet after drying; coating the negative electrode slurry on the negative electrode current collector area, and obtaining a negative electrode sheet after drying; Step 7: In the positive electrode current collector area on the positive electrode sheet, an aluminum sheet tab is placed using silver paste as a binder, and the positive electrode is obtained after drying; in the negative electrode current collector area on the negative electrode sheet, a nickel sheet tab is placed using silver paste as a binder, and the negative electrode is obtained after drying, and the PDMS film is added at the connection between the positive and negative electrodes and the tabs as a fixing layer for connecting the tabs and the battery; Step 8: dripping electrolyte solution between the positive and negative electrodes and on the surfaces of the positive and negative electrodes, covering the surfaces of the positive and negative electrodes with the PDMS film, and obtaining the stretchable flexible lithium-ion battery through sealing, standing, forming and volume separation; There is no order of precedence between step 3 and step 4; there is no order of precedence between step 5 and step 6.

3. The method for preparing a stretchable flexible lithium-ion battery according to claim 2, characterized in that: In the step 1, the mass ratio of the PDMS prepolymer to the cross-linking agent is 10:1; and / or The bubble removal is to place the uniformly mixed PDMS prepolymer and the cross-linking agent into a vacuum drying oven for drying; and / or The density of the mixture on the flexible substrate is 100-200 mg / m 2 ; and / or The drying temperature is 60-100°C.

4. The method for preparing a stretchable flexible lithium-ion battery according to claim 2, characterized in that: In the step 3, the mass ratio of the positive electrode precursor solution to lithium iron phosphate and conductive carbon black is (80-160):(12-20):(1-3).

5. The method for preparing a stretchable flexible lithium-ion battery according to claim 2, characterized in that: In the step 4, the mass ratio of the negative electrode precursor solution to graphene and conductive carbon black is (80-160):(12-20):(1-3).

6. The method for preparing a stretchable flexible lithium-ion battery according to claim 2, characterized in that: In step 5, the coating thickness of the silver paste is 0.05-0.1 mm; the coating speed is 10-20 mm / s; and / or The drying temperature is 100-140° C. and the drying time is 30-50 minutes.

7. The method for preparing a stretchable flexible lithium-ion battery according to claim 2, characterized in that: In step 6, the coating thickness of the positive electrode slurry is 0.05 mm-0.1 mm, and the coating speed is 10-20 mm / s; and / or The coating thickness of the negative electrode slurry is 0.05 mm-0.1 mm, and the coating speed is 10-20 mm / s.

8. The method for preparing a stretchable flexible lithium-ion battery according to claim 2, characterized in that: In step 7, the width of the aluminum sheet tab is 3-6 mm and the thickness is 0.05-0.15 mm; and / or The nickel sheet tab has a width of 3-6 mm and a thickness of 0.05-0.15 mm.

9. The method for preparing a stretchable flexible lithium-ion battery according to claim 2, characterized in that: In step 8, the density of the electrolyte solution is 1.2-1.3 g / cc, the lithium salt of the electrolyte solution is LiPF6, the mass fraction of the lithium salt in the electrolyte solution is 10-15 wt.%, and the solvent of the electrolyte solution is a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 1:1:

1.

10. A stretchable flexible lithium-ion battery, characterized in that: Prepared according to the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of leather integrated full-flexible zinc ion battery

    CN118281371A

  • Flexible battery capable of freely designing shape and preparation method thereof

    CN118645704A

  • Graphene-based lithium-ion battery cathode and preparation method thereof

    CN105489838A

  • Flexible thin film battery and preparation method therefor, circuit board and electronic product

    CN107394273A

  • Stretchable electrode of lithium ion battery and preparation method of stretchable electrode

    CN107565091A